Dude Enterprise: Wiring & Rewiring Service / Muhammad Izz Fauzan Muhammad Fu'at [et al.] - Muhammad Fu'at, Muhammad Izz Fauzan; Muhammad Al Amin, Muhammad Al Amin; Muhammad Hakimi, Muhammad Hakimi; Rahmat, Muhamad Azfar (2016)
As an electrician we installing all wires and electrical appliance that customer order. We also try to give better service to them in order to make them satisfied with our service.